Direct numerical simulation of water–ethanol flows in a T-mixer - Schikarski, Tobias; Peukert, Wolfgang; Avila, Marc (Chemical Engineering Journal, 2017)
The efficient mixing of fluids is key in many applications, such as chemical reactions and nanoparticle precipitation. Detailed experimental measurements of the mixing dynamics are however difficult to obtain, and so predictive numerical tools are helpful in designing and optimizing many processes. If two different fluids are considered, the viscosity and density of the mixture depend often nonlinearly on the composition, which makes the modeling of the mixing process particularly challenging. Hence water-water mixtures in simple geometries such as T-mixers have been intensively investigated, but little is known about the dynamics of more complex mixtures, especially in the turbulent regime. We here present a numerical method allowing the accurate simulation of two-fluid mixtures. Using a high-performance implementation of this method we perform direct numerical simulations resolving the spatial and temporal dynamics of water-ethanol flows for Reynolds numbers from 100 to 2000. The flows states encountered during turbulence transition and their mixing properties are discussed in detail and compared to water-water mixtures.
Keywords: Mixing; T-mixer; Direct numerical simulation; Miscible fluids; Water–ethanol; Transition to turbulence; Turbulent flows

From localized periodic orbits to transients in pipe flow - Avila, Marc; Mellibovsky, Fernando; Roland, Nicolas; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
Hydrodynamic instability in wall bounded shear flows is abrupt and directly results in very complex spatio-temporal patterns even close to onset. This sudden scenario has challenged the application of dynamical systems concepts to describe the onset of turbulence. We present a bifurcation scenario leading from spatially localized relative periodic orbits to chaotic transients in pipe flow.
CRIS-Team Scopus Importer:2020-03-17

Localised exact solutions of pipe flow - Mellibovsky, Fernando; Avila, Marc; Roland, Nicolas; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
Turbulent transition in extended shear flows at low to moderate flow rates is subcritical and takes the form of localised patches of spatio-temporal complexity surrounded by otherwise laminar flow. We study numerically the laminar-turbulent boundary of pipe flow in long domains that allow for spontaneous localisation. We find that the dynamics on the boundary is governed by localised modulated travelling waves that share key structural properties with turbulent puffs.
CRIS-Team Scopus Importer:2020-03-17

Relaminarising fully turbulent pipe flow - Song, Baofang; Avila, Marc; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
We locally applied a control technique to relaminarise fully turbulent pipe flow at Reynolds numbers of up to 20,000. Downstream of the control point the flow remains laminar because of the linear stability of the basic flow and consequentely the drag is reduced substantially. At Re=20000 the pressure drop is reduced by an order of magnitude. We also applied a closely related control mechanism in experiments and managed to relmainarise turbulence at Reynolds number 6000 and the drag dropped by a factor of more than 3. The principal underlying the control scheme in experiments and simulations is closely connected to the self sustaining mechnism of wall bouned turbulence.
CRIS-Team Scopus Importer:2020-03-17

The rise of fully turbulent flow - Song, Baofang; Barkley, Dwight; Mukund, Vasudevan; Lemoult, Grégoire; Avila Canellas, Marc; Hof, Björn (Nature, 2015)
Over a century of research into the origin of turbulence in wall-bounded shear flows has resulted in a puzzling picture in which turbulence appears in a variety of different states competing with laminar background flow. At moderate flow speeds, turbulence is confined to localized patches; it is only at higher speeds that the entire flow becomes turbulent. The origin of the different states encountered during this transition, the front dynamics of the turbulent regions and the transformation to full turbulence have yet to be explained. By combining experiments, theory and computer simulations, here we uncover a bifurcation scenario that explains the transformation to fully turbulent pipe flow and describe the front dynamics of the different states encountered in the process. Key to resolving this problem is the interpretation of the flow as a bistable system with nonlinear propagation (advection) of turbulent fronts. These findings bridge the gap between our understanding of the onset of turbulence and fully turbulent flows.

The speed of turbulent-laminar fronts in pipe flow - Barkley, Dwight; Avila, Marc; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
The speeds of turbulent-laminar interfaces in pipe flow are studied theoretically, and through numerical simulations of the Navier-Stokes equations and laboratory experiments. A particular focus is the continuous, but non-smooth transition from localized puffs to expanding slugs. Different interfaces within the slug regime are discussed.
CRIS-Team Scopus Importer:2020-03-17

Topology optimization of unsaturated flows in multi-material porous media: Application to a simple diaper model - Wein, Fabian; Chen, Nan; Iqbal, Naveed; Stingl, Michael; Avila, Marc (Communications in Nonlinear Science and Numerical Simulation, 2019)
We present a mathematical approach to optimize the material distribution for fluid transport in unsaturated porous media. Our benchmark problem is a simplified diaper model as an exemplary liquid absorber. Our model has up to three materials with vastly different properties, which in the reference configuration are arranged in parallel layers. Here, swelling is neglected and the geometry of a swollen diaper is assumed and treated as a porous medium of high porosity. The imbibition process is then simulated by solving an unsaturated flow problem based on Richards’ equation. Our aim is to maximize the amount of absorbed liquid by redistributing the materials. To this end, a density based multi-material topology optimization (based on the well known SIMP model) is performed. A sensitivity analysis for the nonlinear transient problem is provided, which enables the application of first order optimization solvers. We perform two- and three-material optimization and discuss several variants of the problem setting. We present designs with up to 45% more absorbed liquid compared to the reference configuration.
CRIS-Team Scopus Importer:2019-06-28
Keywords: Imbibition; Optimization; Permeability; Porous media

Transition to magnetorotational turbulence in Taylor-Couette flow with imposed azimuthal magnetic field - Guseva, Anna; Willis, A. P.; Hollerbach, Rainer; Avila, Marc (New Journal of Physics, 2015)
The magnetorotational instability (MRI) is thought to be a powerful source of turbulence and momentum transport in astrophysical accretion discs, but obtaining observational evidence of its operation is challenging. Recently, laboratory experiments of Taylor-Couette flow with externally imposed axial and azimuthal magnetic fields have revealed the kinematic and dynamic properties of the MRI close to the instability onset. While good agreement was found with linear stability analyses, little is known about the transition to turbulence and transport properties of the MRI. We here report on a numerical investigation of the MRI with an imposed azimuthal magnetic field. We show that the laminar Taylor-Couette flow becomes unstable to a wave rotating in the azimuthal direction and standing in the axial direction via a supercritical Hopf bifurcation. Subsequently, the flow features a catastrophic transition to spatio-temporal defects which is mediated by a subcritical subharmonic Hopf bifurcation. Our results are in qualitative agreement with the PROMISE experiment and dramatically extend their realizable parameter range. We find that as the Reynolds number increases defects accumulate and grow into turbulence, yet the momentum transport scales weakly.
UnivIS-Import:2017-12-18:Pub.2015.tech.ITC.stmmec.transi
Keywords: magnetorotational instability; TaylorCouette flow; MHD